Conspiracy beliefs and the preference for natural treatments in medical decision-making - Lorenzo Gagliardi (Acta Psychologica, 2025)
Naturalness bias—the tendency to prefer natural products over synthetic alternatives—is a widespread phenomenon in consumer and health decision-making. Despite the lack of a clear scientific definition, the label “natural” evokes strong intuitive associations with purity, safety, and moral value. Interestingly, these associations often overlap with conspiratorial thinking, particularly in contexts where synthetic medical treatments are portrayed as harmful or profit-driven. This paper provides a comprehensive literature review on the relationship between naturalness bias and conspiracy beliefs. We included both empirical and theoretical sources across psychology, medicine, and health communication. Based on this review, we propose two complementary theoretical explanations for the causal link between the two phenomena, which go both directions: a consequential account, where conspiracy beliefs foster distrust in institutional medicine and encourage natural preferences; and a justificatory account, where intuitive preferences for natural options are rationalized by the means of conspiratorial narratives. In addition, we identify common psychological antecedents—such as Manichean worldviews, perceived lack of control, and intuitive cognitive styles—that may help explain the co-occurrence of these two tendencies. These insights offer new perspectives on the role of conspiracy beliefs in shaping health behaviors and medical decision-making.